2020
DOI: 10.1080/15476286.2020.1767455
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs as tumor cell intrinsic factors that affect cancer immunotherapy

Abstract: Long noncoding RNAs (lncRNAs) have been found to associate with all major types of malignancies and play important roles in regulating several hallmarks of cancer by interacting with proteins, DNA, and RNA. The possible functions of lncRNAs and their roles in the regulation of tumour growth will be reported and discussed in the present review. In our recent report, based on genetic mice models and a series of systematic analyses, we suggested that lncRNAs also play critical roles in the regulation of antigen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…This is quite different from the direct effects of regular lncRNAs on the biological functions of tumor cells [ 12 , 30 ]. Therefore, the expression levels of IRlncRs often correlate with clinical outcomes such as sensitivity to immunotherapy and prognosis [ 13 ], highlighting their advantage as tumor biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is quite different from the direct effects of regular lncRNAs on the biological functions of tumor cells [ 12 , 30 ]. Therefore, the expression levels of IRlncRs often correlate with clinical outcomes such as sensitivity to immunotherapy and prognosis [ 13 ], highlighting their advantage as tumor biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a subset of lncRNAs act as immune-related lncRNAs (IRlncRs) by regulating immune responses in the tumor microenvironment. This subset of lncRNAs has been shown to play a key role in modulating tumor immunosurveillance, immune cell infiltration into the tumor microenvironment, and sensitivity of cancer cells to immunotherapy treatment [ 12 , 13 ]. Cao et al identified an immune-related five-lncRNAs signature positively correlated with tumour immune cell infiltration and the poor prognosis in bladder cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that p53 induces the alternative transcript PVT1B during genotoxic stress, which helps p53-mediated tumor growth restriction in vivo by regulating the transcription of the nearby MYC genes. Alternatively, it has also been shown that the lncRNA LINC02525, which is upregulated in neuroblastomas and interacts with the ribosomal protein RPL35 to activate the translation of E2F1, maintains the stability of the NMYC protein, and causes ERK protein phosphorylation, plays an obvious oncogenic role [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maternally expressed gene 3 (lncRNA MEG3) is one of these tumor suppressor lncRNAs that have received a lot of attention [ 13 ]. Researchers have demonstrated that the lncRNA MEG3 could control p53 expression to act as a tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, there has been increasing evidence that lncRNAs play a key role in regulating cancer proliferation, metastasis, cell cycle, and programmed death [10][11][12][13]. LncRNA is a class of RNA molecules with transcripts longer than 200 nucleotides.…”
Section: Introductionmentioning
confidence: 99%